Humic fractions of forest, pasture and maize crop soils resulting from microbial activity - Tavares, Rose Luiza Moraes [UNESP]; Nahas, Ely [UNESP] (Sociedade Brasileira de Microbiologia, 2014)
Humic substances result from the degradation of biopolymers of organic residues in the soil due to microbial activity. The objective of this study was to evaluate the influence of three different ecosystems: forest, pasture and maize crop on the formation of soil humic substances relating to their biological and chemical attributes. Microbial biomass carbon (MBC), microbial respiratory activity, nitrification potential, total organic carbon, soluble carbon, humic and fulvic acid fractions and the rate and degree of humification were determined. Organic carbon and soluble carbon contents decreased in the order: forest > pasture > maize; humic and fulvic acids decreased in the order forest > pasture=maize. The MBC and respiratory activity were not influenced by the ecosystems; however, the nitrification potential was higher in the forest than in other soils. The rate and degree of humification were higher in maize soil indicating greater humification of organic matter in this system. All attributes studied decreased significantly with increasing soil depth, with the exception of the rate and degree of humification. Significant and positive correlations were found between humic and fulvic acids contents with MBC, microbial respiration and nitrification potential, suggesting the microbial influence on the differential formation of humic substances of the different ecosystems.
Keywords: humification; microbial biomass carbon; potential nitrification; respiratory activity